Collective action in pest management - Ravnborg, Helle Munk (International Food Policy Research Institute, 2004)
Since crop and animal pests destroy farmers' production, this brief looks at the ways pests can be controlled either by individual farmers, by public programmes, or by neighbors working together. This brief examines those cases where technology is not the answer and where farmer collaboration of farmers is the essential element in successful management of pests. The author writes, Because of the transboundary nature of many pest problems, technical solutions?whether based on the use of pesticides or on biological principles?are rarely sufficient. She concludes that extension programs, like farmer field schools, should (1) promote an understanding of the spatial dimensions of pest ecology and (2) provide communication techniques that will enable groups of farmers to approach neighboring farmers to invite them to take part in coordinated pest management. -- from Text.